Volunteer Program Skrining Dan Percepatan Vaksinasi Covid-19 Pada Ibu Hamil Di Surabaya - Ma'rifah, Umi; Kunsah, Baterun; Mardiyah, Nova Elok; Anifah, Fulatul (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
The increasing number of Covid-19 cases, especially the presence of a new Delta variant which causes a risk of severe symptoms in pregnant women, the Indonesian government has established a screening program and implementation of the Covid-19 vaccination as stated in circular letter HK.02.01/I/2007/2021. Based on preliminary studies carried out on pregnant women in the city of Surabaya, there are 90% percent of pregnant women who are still hesitant and afraid to vaccinate. One form of effort being made is the development of an application that facilitates screening and accelerates vaccination of pregnant women, namely the VMil application. The purpose of this study was to find out how the Volunteer program through the V-MiL application affects pregnant women in carrying out Covid-19. This type of research is pre-experimental with one group pre-test and post test design. The dependent variable is the respondent's participation in the implementation of the Covid-19 vaccine, while the independent variable is intervention by volunteers using the V-MiL application. The research sample for pregnant women who had not been vaccinated was 40 people using a purposive sampling technique. Data collection with questionnaires and interviews. The results of the study the majority of respondents aged 21-30 years (58%), gestational age 13-27 weeks (78%). After the intervention the respondents had good knowledge 18 (45%), lack of knowledge 22 (55%), negative attitude positive attitude 16 (40%), negative attitude 24 (60%), strong motivation 15 (38%), weak motivation 25 (63%) to vaccinate. Respondents did the Covid-19 vaccine as many as 15 (38%) and 25 (63%) respondents did not do the vaccine. Analysis using the Paired sample T test obtained a value of λ of 0.001 <0.005 which indicated that there was a significant influence on the intervention given by volunteers to the respondents. Keywords                    : Volunteers, Covid-19 Vaccines, Pregnant Women